NEED ANALYSIS AND ITS IMPLEMENTATION OF ENGLISH SKILLS IN FRONT OFFICE DEPARTMENT OF HOTEL INDUSTRY - eko aprianto (Fakultas Ilmu Budaya, Universitas Brawijaya, 2018)
Abstract English as international language plays an important role, such as establish social communication or relationship with other people in the world. If we have good ability in English, it will be easy for us to conduct an international relation with all nations in the world. Hotel is one of tourism industry that has relationship in English communication where the process of communication happens as services given to the guest. The research design used in this study is descriptive qualitative, by giving description about the need of English skill use by Front Office department hotel in Malang. The researcher limited the hotels only the members of Hotel and Restaurant Association (PHRI) in Malang. The respondents of this study were taken from 88 hotels in Malang who has 3 years up working experience in Front Office Department. Finally, the researcher found that speaking skill were maximally used in hotel front office. So, as the implication of this study in the educational field is the university curriculum especially for speaking class should be appropriate with the students need. The implementation of teaching material in speaking class should also base on the needed of stakeholders in order to the students ready to face the challenging of the world. Key Words: English language skills, English for specific purpose, Hotel Front Office